The role of imprinting genes’ loss of imprints in cancers and their clinical implications - Xie, Guojing; Si, Qin; Zhang, Guangjie; Fan, Yu; Li, Qinghua; Leng, Ping; Qiao, Fengling; Liang, Simin; Yu, Rong; Wang, Yingshuang (Frontiers in Oncology, 2024)
Genomic imprinting plays an important role in the growth and development of mammals. When the original imprint status of these genes is lost, known as loss of imprinting (LOI), may affect growth, neurocognitive development, metabolism, and even tumor susceptibility. The LOI of imprint genes has gradually been found not only as an early event in tumorigenesis, but also involved in progression. More than 120 imprinted genes had been identified in humans, in this review, we summarized the most studied LOI of two gene clusters and 13 single genes in cancers. We focused on the roles they functioned like growth suppressors, anti-apoptosis, sustaining proliferative signaling or inducing angiogenesis, the molecular pathways they regulated, and especially their clinical significances. It is notable that 12 combined forms of multi-genes LOI, 3 of which has already been used as diagnostical models, achieving well sensitivity, specificity, and accuracy. In addition, the methods used for LOI detection in existing research are classified into detection of biallelic expression (BAE), differentially methylated regions (DMRs) methylation and single nucleotide polymorphisms (SNPs). These all indicated that the detection of imprinting genes LOI have potential clinical significance in cancer diagnosis, treatment, and prognosis.